Recurrence and Frequency of Disturbance have Cumulative Effect on Methanotrophic Activity, Abundance, and Community Structure - Ho, Adrian; van den Brink, Erik; Reim, Andreas; Krause, Sascha M. B.; Bodelier, Paul L. E. (Frontiers in Microbiology, 2016)
Alternate prolonged drought and heavy rainfall is predicted to intensify with global warming. Desiccation-rewetting events alter the soil quality and nutrient concentrations which drive microbial-mediated processes, including methane oxidation, a key biogeochemical process catalyzed by methanotrophic bacteria. Although aerobic methanotrophs showed remarkable resilience to a suite of physical disturbances induced as a single event, their resilience to recurring disturbances is less known. Here, using a rice field soil in a microcosm study, we determined whether recurrence and frequency of desiccation-rewetting impose an accumulating effect on the methanotrophic activity. The response of key aerobic methanotroph subgroups (type Ia, Ib, and II) were monitored using qPCR assays, and was supported by a t-RFLP analysis. The methanotrophic activity was resilient to recurring desiccation-rewetting, but increasing the frequency of the disturbance by two-fold significantly decreased methane uptake rate. Both the qPCR and t-RFLP analyses were congruent, showing the dominance of type Ia/Ib methanotrophs prior to disturbance, and after disturbance, the recovering community was predominantly comprised of type Ia (Methylobacter) methanotrophs. Both type Ib and type II (Methylosinus/Methylocystis) methanotrophs were adversely affected by the disturbance, but type II methanotrophs showed recovery over time, indicating relatively higher resilience to the disturbance. This revealed distinct, yet unrecognized traits among the methanotroph community members. Our results show that recurring desiccation-rewetting before a recovery in community abundance had an accumulated effect, compromising methanotrophic activity. While methanotrophs may recover well following sporadic disturbances, their resilience may reach a ‘tipping point’ where activity no longer recovered if disturbance persists and increase in frequency.